2009
DOI: 10.1093/carcin/bgp010
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine stimulates pancreatic cancer xenografts by systemic increase in stress neurotransmitters and suppression of the inhibitory neurotransmitter  -aminobutyric acid

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a leading cause of cancer mortality in Western countries. We have shown previously that four representative human PDAC cell lines were regulated by beta-adrenoreceptors via cyclic adenosine 3',5'-monophosphate (cAMP)-dependent signaling. In the current study, we have tested the hypothesis that nicotine stimulates the growth of PDAC xenografts in nude mice by increasing the systemic levels of the stress neurotransmitters adrenaline and noradrenaline, which are the phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 39 publications
6
67
1
Order By: Relevance
“…In contrast, interpretation of previous studies that investigated pancreatic tumor growth in flank was limited by the context of non-physiological intercellular interactions [5558]. To better understand β-adrenergic regulation of pancreatic cancer onset it will be important to investigate the effects of chronic stress in transgenic models that spontaneously develop pancreatic cancer [59].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, interpretation of previous studies that investigated pancreatic tumor growth in flank was limited by the context of non-physiological intercellular interactions [5558]. To better understand β-adrenergic regulation of pancreatic cancer onset it will be important to investigate the effects of chronic stress in transgenic models that spontaneously develop pancreatic cancer [59].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a previous study by our laboratory showed a significant nicotine-induced growth promotion of pancreatic cancer xenografts associated with increased levels of noradrenaline, adrenaline and cAMP in blood and xenograft tissues as well as an induction of p-CREB and p-ERK in xenograft tissues. These changes were interpreted as indirect effects of such systemic neuroendocrine responses (28). Our current in vitro experiments are not influenced by this systemic neuroendocrine effect of nicotine and unequivocally show that two pancreatic cancer cell lines as well as immortalized pancreatic duct epithelia synthesized and released their own noradrenaline and adrenaline in response to nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that γ-aminobutyric acid (GABA) inhibited the proliferation and migration of pancreatic cancer cells in vitro via GABA-B receptor mediated inhibition of adenylyl cyclase (20). GABA also reversed the growth promoting effects of nicotine on pancreatic cancer xenografts by reducing tumor cAMP levels (28). GABA has been safely used as a nutritional supplement for many years and selective GABA-B-receptor agonists are widely used for the pharmacological management of spastic pain after spinal injuries and spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Gene-knockdown of Gα i -coupled GABA-B receptors (GABA-B-Rs) blocked these effects of GABA while transient overexpression of GABA-B-Rs enhanced these responses to GABA, identifying the Gα i -mediated inhibition of adenylate cyclase activation as the underlying mechanism [11]. In accord with these in vitro findings, the progression of PDAC xenografts in athymic nude mice was significantly inhibited in the absence and presence of chronic exposure to nicotine or social stress by treatment of the animals with GABA in the drinking water [12, 24]. GABA treatment also enhanced the responsiveness of PDAC xenografts to the cancer therapeutic agent celecoxib in the absence and presence of social stress [25].…”
Section: Introductionmentioning
confidence: 99%